The Food Intake Recording Software System is Valid Among Fourth-grade Children - BARANOWSKI, TOM; ISLAM, NOEMI; BARANOWSKI, JANICE; CULLEN, KAREN W.; MYRES, DAWNELL; MARSH, TARA; de MOOR, CARL (Journal of the American Dietetic Association, 2002)
Objectives To assess the validity of the Food Intake Recording Software System (FIRSSt) against observation of school lunch and a 24-hour dietary recall (24hDR); and to test the effects of sequencing, observation and a hair sample as a bogus pipeline on accuracy of dietary report. Design Six-group design systematically varying sequence of self-report (FIRSSt vs 24hDR), observation of school lunch, and hair sample as a bogus pipeline manipulation, with random assignment of participants. Subjects/setting 138 fourth-grade students in 2 elementary schools. Main outcome measures Accuracy of reported food consumption was measured in terms of matches, intrusions, and omissions among the FIRSSt, 24hDR, and as observed at school lunch. Students also completed self-report of performance with FIRSSt. Statistical analysis performed t tests, Pearson correlations, analysis of variance, factor analysis. Results When compared with school lunch observation for one meal, FIRSSt attained 46% match, 24% intrusion, and 30% omission rates, while a dietitian-conducted 24hDR obtained 59% match, 17% intrusion, and 24% omission rates. FIRSSt attained 60% match, 15% intrusion, and 24% omission rates against 24hDR for all meals in the previous day. There was no evidence of sequence of assessment affecting accuracy indicators, but there was a weak effect of school lunch observation on percent intrusions. Obtaining a hair sample reduced the omission rate for FIRSSt vs 24hDR and increased the match rate for 24hDR vs observation, thereby enhancing this as a bogus pipeline procedure. Children generally enjoyed completing FIRSSt. Hispanic children were more likely to report problems using FIRSSt. Applications/conclusions FIRSSt is somewhat less accurate than a dietitian-conducted 24hDR. However, this lower-cost procedure provides a promising method for assessing diet among children. Observation of consumption at school lunch may be reactive and artificially increase agreement. Obtaining a hair sample as a bogus pipeline may be a valuable technique for enhancing the accuracy of dietary assessment among children. J Am Diet Assoc. 2002; 102:380–385.